2021
DOI: 10.1002/open.202100072
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Pitfalls in Comparison of Activity and Selectivity of Solid Catalysts for Electrochemical HMF Oxidation

Abstract: Electrocatalytic oxidation of 5‐hydroxymethylfurfural (HMF) offers a renewable approach to produce the value‐added platform chemical 2,5‐furandicarboxylic acid (FDCA). The key for the economic viability of this approach is to develop active and selective electrocatalysts. Nevertheless, a reliable catalyst evaluation protocol is still missing, leading to elusive conclusions on criteria for a high‐performing catalyst. Herein, we demonstrate that besides the catalyst identity, secondary parameters such as materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Another study showed that the maximum value of FE, yield, and production rate can be reached in 1 m KOH, which might be due to electrochemical and nonelectrochemical losses of HMF to unwanted side products at higher electrolyte concentration. [50] However, the situation is different for electrooxidation of HMF to DFF. [29] The selectivity and yield of DFF increased significantly with the decreasing pH which can be attributed to the stable aldehyde group of nonhydrate form by the resonance with aromatic nucleus under mild alkaline or neutral conditions.…”
Section: Electrolyte Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study showed that the maximum value of FE, yield, and production rate can be reached in 1 m KOH, which might be due to electrochemical and nonelectrochemical losses of HMF to unwanted side products at higher electrolyte concentration. [50] However, the situation is different for electrooxidation of HMF to DFF. [29] The selectivity and yield of DFF increased significantly with the decreasing pH which can be attributed to the stable aldehyde group of nonhydrate form by the resonance with aromatic nucleus under mild alkaline or neutral conditions.…”
Section: Electrolyte Concentrationmentioning
confidence: 99%
“…[ 46 ] Besides, Cu‐sheet was proved to be a good potential catalyst for HMF oxidation but cannot be applied as an inert support. [ 50 ] It is worth noting that the reactive inertia of conductive substrate is not considered in industry, but its structural stability should be paid attention to. Here, we suggest to select the appropriate catalyst substrate based on the following two points: one is the physicochemical stability of 3D conductive substrate and the other is selectivity for the oxidation and hydrogenation of H 2 O and HMF.…”
Section: Operating Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalysts should be selected from abundant metals for sustainability and cost reasons if sufficiently high activities could be achieved. There is a number of reports on the electrooxidation of HMF to FDCA on different electrodes, some of rather complex nature, achieving current densities ranging from a few ten to hundreds mA cm −2 , (for a survey, see Table S1), which are, however, often difficult to compare [15] . Electrolysis at either high current density (>300 mA cm −2 ) or high HMF concentrations for efficient and selective FDCA synthesis approaching industrial conditions remains less explored.…”
Section: Figurementioning
confidence: 99%
“…Unlike fossil feedstocks, biomass typically feature high oxygen content (40−45 wt.%) 5 , making it an ideal starting material to produce valuable oxygenates, such as formic acid 6 , 2,5-furandicarboxylic acid (FDCA) 7 9 , furoic acid 10 , and saccharic acids 11 . However, owning to the inherently high reactivity of oxygen-containing functional groups in biomass derivatives (e.g., aldehyde, ketone), the upgrading technologies often suffer from undesired degradation under extreme reaction conditions (e.g., high-temperature, basic or acidic medium), which is further aggravated for concentrated feedstock 12 , 13 . A long-recognized example is sugar degradation to a portfolio of organic acids in alkaline solution, owning to the rearrangement of polyhydroxy aldehyde/ketone structure of sugar under base catalysis 14 , 15 , a first-order reaction with respect to the sugar concentration 16 .…”
Section: Introductionmentioning
confidence: 99%